Surgical Procedures Requiring Hospitalization and Perioperative Management for Patients with Hereditary Bleeding Disorders - Hyeun Su Seo; Won Kee Ahn; Seung Min Hahn; Jung Woo Han; Chuhl Joo Lyu (The Korean Society of Pediatric Hematology-Oncology, 2022)
Background : : Hemophilia requires a lifetime care for bleeding control and complications. Although patients diagnosed with hemophilia receive factor replacement, they also experience a variety of medical problems as they age. Elective surgery can be performed through appropriate factor replacement during and after surgery. However, for patients with inhibitors, this remains a problem to be overcome. Methods : : Patients treated for congenital bleeding disorders between 2008 and 2021 were enrolled in this study. The patients were classified according to the type, severity, and presence of inhibitors. The patients underwent planned coagulation factor replacement depending on the type of surgery. Results : : A total of 232 patients treated for congenital bleeding disorders were enrolled. Among them hemophilia A was most prevalent, followed by hemophilia B. In total, 78 of the patients underwent surgery, including 31 major and 55 minor surgeries. Orthopedic surgery was the most common surgery, and patients with inhibitors had significantly more postoperative hospitalization days. Nine patients were incidentally diagnosed. Twelve patients with hemophilia with inhibitors underwent surgery, and 6 of them experienced post-operative complications. Conclusion : : Proper surgical planning and monitoring with a multidisciplinary team will be required for appropriate perioperative management of patients with hemophilia, especially in patients with inhibitor and elderly hemophilia patients.